Modelling relationships between agility, lean, resilient, green practices in cold supply chains using ISM approach - Al-Refaie, Abbas; Al-Tahat, Mohammad; Lepkova, Natalija (Technological and Economic Development of Economy, 2020)
This study aims at identifying the key agile, lean, resilient and green practices that influence capability of cold supply chain (CSC) using Interpretive Structural Modelling (ISM) technique. Various measures of lean, green, resilient, and agile practices in CSC were identified from previous studies and experts’ opinions. Contextual relationships between practice measures were established via brainstorming session. Measures were then classified based on their driving and dependence powers. The results showed that measures of lean, green, resilient, and agile practices in CSC can be organized in a six-level structural model. Moreover, highly dependent measures at top level in CSC model are operational costs and customer satisfaction, whereas the highly driving at most bottom level of this model are ISO 14001 implementation and government support system for green cold supply chain. Validity of CSC model was assessed in three CSC firms; food, pharmaceutical, and Third Party logistics firms. In conclusion, measures emerging with higher driving power and those with high dependence in ISM hierarchy contribute significantly to enhancing capability of CSC. The proposed ISM may support decision makers in prioritization improvement efforts and achieving effective CSC.